Sextortion: A Scoping Review. - Ray, Alana; Henry, Nicola (Trauma, Violence & Abuse, 2025)
Sextortion refers to making threats to share nude or sexual images to coerce the victim into complying with certain demands, such as paying a ransom, sharing intimate images, or engaging in unwanted acts. Sextortion occurs in a diverse range of contexts, including intimate partner abuse, cyberbullying, sexuality or sex worker "outing," online dating, "cybersex," sex trafficking, online sexual exploitation of children, computer hacking, and organized crime. Despite the heightened media focus, few studies have measured the prevalence, nature, and impacts of sextortion. We conducted a scoping review with the aim of providing a comprehensive overview of existing empirical research on sextortion victimization and perpetration among youth and adults. In total, 24 studies were identified based on predefined eligibility criteria. We found that studies focusing on youth reported prevalence ranging from 0.7% to 5.0%, while studies involving adults ranged from 4.0% to 18.7%. The review found that young people and sexual minorities are more likely to experience victimization, while men, young people, and sexual minorities are more likely to self-report engaging in sextortion offending. The review found that perpetrators are more likely to be intimate partners or other known persons as opposed to strangers and that there was an overlap between sextortion perpetration and victimization. Finally, we also found that sextortion can result in significant harms, and that reporting and help-seeking remain very low due to shame, fear, and negative perceptions of police and digital platforms. The findings highlight existing gaps and provide recommendations for future research, policy, and practice.